RELEVANSI ALIRAN FILSAFAT REALISME DALAM PEMBELAJARAN ABAD 21 MELALUI MODEL PEMBELAJARAN CITIZEN SCIENCE PROJECT (CSP) - Sahla Sahira; Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The current learning paradigm needs to be designed in such a way as to shape students to achieve the goals of the 21st century education system. The school of philosophy, which has relevance to the challenges of 21st century learning, is the realism school of philosophy. Realism is a real depiction of an external world that has a real existence that can be accessed through observation and experience. The philosophy of realism emphasizes understanding the real world through observation and direct experience. Citizen Science Project (CSP) is a learning model that involves students in scientific research projects that are relevant to real life and involve community assistance. This research uses a qualitative descriptive approach with library methodology or literature review. This research data was obtained from library sources, documents and scientific journals. The results of this research are that the realism philosophy has very significant relevance in 21st century learning, especially through the application of the Citizen Science Project (CSP) model.